Analysis of Massive Transfusion Protocol Utilization in Trauma Across Sociodemographic Groups - Monique Arnold; Bharti Sharma; Matthew Conn; Kate Twelker; Navin D. Bhatia; George Agriantonis; Jasmine Dave; Juan Mestre; Zahra Shafaee; Jennifer Whittington (Medicina)
Background and Objectives: Blood shortages are a national crisis, creating dangerous scenarios for patients requiring the use of a massive transfusion protocol (MTP). A judicious use of blood products is critical to rescue salvageable patients while refraining from unnecessary MTP to save precious resources. This study examines effect of trauma characteristics, socioeconomic variables and markers of futility on the likelihood of activating and receiving MTP in the trauma setting. Materials and Methods: In this retrospective study, emergency department (ED) trauma activations from a database of an urban Level I trauma center were analyzed from 1 January 2017 to 30 June 2022, inclusive. In-ED mortality, RBC transfusion volumes during initial resuscitation, patient sociodemographic data, and trauma event factors were analyzed. The primary outcomes were the dichotomous outcomes of MTP activation and MTP transfusion. Univariable analyses and logistic regressions were conducted, with class balancing sensitivities applied to the multivariable regressions to adjust for imbalance in the data. p < 0.05 was considered statistically significant. Results: Among the 8670 trauma activations, there was a 0.3% in-ED mortality rate. MTP activation and MTP transfusion were associated with higher in-ED mortality rates (3.8% and 15.4%, respectively, compared to 0.2% without MTP). Younger patients, male patients, and Medicaid recipients were more likely to undergo MTP activation; Medicare patients were less likely. Penetrating trauma substantially increased the likelihood of both MTP activation (odds ratio (OR) 5.81) and transfusion (OR 3.63). The logistic regression models identified the presence of penetrating trauma, lower probability of survival, and age as the most important covariates. Models demonstrated high discriminatory value (area under the curve (AUC) of the receiver operating characteristic curve (ROC) of 0.876 for MTP activation, 0.935 for MTP transfusion) and precision (0.974 for activation, 0.994 for transfusion), with class balancing further improving model performance and precision scores. Conclusions: These results are significant as assessing the futility of MTP should be equitable, and future transfusion guidelines should consider salvageability in cases with a low probability of survival despite age and mechanism.